Representações sociais, mídia e violência : a “construção” do migrante e da migração venezuelana em Roraima por meio dos websites da Folha de Boa Vista e Folha de S. Paulo - Mota, Daniele Monteiro (2019)
The object of this dissertation is the social representations about the migration and the Vene-zuelan migrants built from the reports published from 2016 to 2017 in the newspapers, online version, Folha de Boa Vista and Folha de São Paulo, as well as the speeches reproduced by its readers. For this, we used the content analysis method (CA) whose task was performed in subsequent steps, but in a dialectical process. The first stage of the research was the pre- exploration of the material on websites; the second, the election of units of analysis (or units of meanings) that were organized at the clipping level with the selection of sentences, sen- tences or paragraphs; The third phase consisted of the categorization and subcategorization of the reports that finally outlined the research path. The contribution of the theories of Social Representation, migration and the media were fundamental to the analytical process. Thus, the results indicated that the social representation performed by the newspapers reproduce stereo- types and stigmas, and above all, stimulate and reinforce the processes of rejection and denial of the “other” contributing to generate a climate of permanent conflict in local society. From the point of view of the comments it could be inferred that there is a lack of conformity re- garding the entry and presence of Venezuelan migrants in Roraima, which in turn causes a distinctive deepening of cultural relations on the border between Brazil and Venezuela, as well as the unmasking Roraima, as well as Brazil, as a “cordial”, receptive state and the city of Boa Vista as “city with open arms” (city hall slogan).